Longitudinal associations between leisure activities and subjective happiness among middle-aged and older adults people in China: national cohort study - Feng, Chengkai; Shi, Zhenguo; Tian, Yuge; Ma, Chao; Sun, Qian (Frontiers in Public Health, 2024)
Background Leisure activities serve as key measures to enhance the subjective happiness of middle-aged and older adults individuals and to positively address the challenges of an aging society; however, the trajectory of changes in their participation in leisure activities and how these changes relate to shifts in subjective happiness have not been adequately explored. Methods This study selected data from the China Health and Aging Longitudinal Study (CHARLS), which included a total of 5,190 middle-aged and older adults people. Linear and nonlinear latent growth models, parallel latent growth models and cross-lagged models were constructed to investigate the influence and lagged relationship between the trajectory of changes in the level of participation in leisure activities on the trajectory of changes in the subjective well-being of middle-aged and older adults people. Results The initial level of physical activity participation of middle-aged and older adults people significantly predicted the initial level (β = 1. 203, p < 0.001) and rate of change (β = −0.138, p = 0.016) of their subjective well-being, and the trajectory of change of middle-aged and older adults people’s physical activity also significantly predicted the rate of change of their subjective well-being (β = 0.582, p = 0.003). Meanwhile, the initial level of social activity of middle-aged and older adults people also effectively predicted the initial level of their subjective well-being (β = 0.048, p < 0.001). At the same time, the covariates (gender, age, level of education, marital status, chronic disease) also predicted the initial level and rate of change of leisure activity participation level and subjective well-being. Finally, the cross-lagged model test confirmed the predictive effect of leisure activity participation level on subjective well-being of middle-aged and older adults people. Conclusion This study confirms that the level of participation in leisure activities of Chinese middle-aged and older adults people has a significant predictive effect on their subjective happiness and that there is a significant correlation between the trajectory of changes in the level of participation in leisure activities and the trajectory of changes in subjective happiness.